2022
DOI: 10.3390/ijerph191711097
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Degradation Pathways of Microbacterium resistens MZT7, A Novel 17β-Estradiol-Degrading Bacterium

Abstract: Due to the ecotoxicity of 17β-estradiol (E2), residual E2 in the environment poses potential risks to human and animal health and ecosystems. Biodegradation is considered one of the most effective strategies to remove E2 from the environment. Here, a novel, efficient E2-degrading bacterial strain Microbacterium resistens MZT7 was isolated from activated sludge and characterized. The genome of strain MZT7 contained 4,011,347 bp nucleotides with 71.26% G + C content and 3785 coding genes. There was 86.7% transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…It is well known that the E2 biodegradation occurs mainly through enzyme catalysis. In most of the reported E2-degrading bacteria, enzyme-catalyzed conversion of E2 to estrone (E1) is considered as the first reaction step in E2 degradation [ 7 , 20 22 ]. This step of reaction is the key and restriction step for E2 to be biodegraded [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that the E2 biodegradation occurs mainly through enzyme catalysis. In most of the reported E2-degrading bacteria, enzyme-catalyzed conversion of E2 to estrone (E1) is considered as the first reaction step in E2 degradation [ 7 , 20 22 ]. This step of reaction is the key and restriction step for E2 to be biodegraded [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microbacterium resistens MZT7 ( M. resistens MZT7) was isolated from dairy farm activated sludge and was subjected to whole genome sequencing (Accession number CP082781) [ 22 ]. Previous studies have shown that strain MZT7 can degrade E2 to E1 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation